Partition and Aesthetic Expression: A Comparative Reading of Manto’s Toba Tek Singh and Malik’s Savage Anguish - Dr Shivajit Dutta (ILN Journal: Indian Literary Narratives, 2025)
The seminal short stories based on the Partition of India, Saadat Hasan Manto’s Toba Tek Singh and Syed Abdul Malik’s Savage Anguish (Bibhatsa Bedona), have several thematic and artistic parallels between them. These short stories employ unique aesthetic functions to unveil the absurdity, trauma, and moral disintegration that were unleashed by the Partition. Manto situates his satirical narrative within a lunatic asylum, symbolizing the broader insanity of a divided nation, while Malik exposes the same moral decay through the perspective of a self-centered middle-class narrator confronting the naked realities of communal violence. The article calls attention to their craftsmanship in narrative technique and in the symbolic use of madness, nakedness, and light to expose bitter social realities lying underneath. Elements like irony, suspense, and the contrast between appearance and reality reinforce the emotional and ethical impact of the narratives. Both writers transform socio-historical tragedy into a profound artistic statement evoking pathos and self-reflection. The humanist vision of these writers questions the inhumanity of communal hatred, rendering these stories enduring reminders of the irrationality of Partition and the need for compassion in a growingly divisive world.